In the shadow of Vesuvius - Jampel, Barbara (WQED/Pittsburg : National Geographic Society, 1987)
Presents the history of the volcano Vesuvius which has erupted fifty times since the Roman era, and shows several other volcano sites located near human dwellings. Give a brief summary of plate tectonics and tells how scientists try to predict future eruptions.
Keywords: Volcanic activity prediction; Vesivius (Italy) -- History